2015
DOI: 10.1021/acs.jafc.5b03018
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic Acid, Abscisic Acid, and Salicylic Acid Are Involved in the Phytoalexin Responses of Rice to Fusarium fujikuroi, a High Gibberellin Producer Pathogen

Abstract: Fusarium fujikuroi, the causal agent of bakanae disease, is the main seedborne pathogen on rice. To understand the basis of rice resistance, a quantitative method to simultaneously detect phytohormones and phytoalexins was developed by using HPLC-MS/MS. With this method dynamic profiles and possible interactions of defense-related phytohormones and phytoalexins were investigated on two rice cultivars, inoculated or not with F. fujikuroi. In the resistant cultivar Selenio, the presence of pathogen induced high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 46 publications
1
63
0
Order By: Relevance
“…These can act as phytoalexins during pathogenic interactions. A recent study by Siciliano et al (2015) suggested that high JA, SA, and abscisic acid (ABA) could counteract Fusarium responses in rice plants. This study also showed that RWL-1 inoculation activated the endogenous physiological apparatus to influence the disease-causing ability of F. oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…These can act as phytoalexins during pathogenic interactions. A recent study by Siciliano et al (2015) suggested that high JA, SA, and abscisic acid (ABA) could counteract Fusarium responses in rice plants. This study also showed that RWL-1 inoculation activated the endogenous physiological apparatus to influence the disease-causing ability of F. oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…Original standards of resveratrol (purity ≥99%), polydatin (purity ≥95%), and viniferin (purity ≥95%), purchased from Sigma-Aldrich, were used to prepare the calibration curves. Similarly, the ABA content was quantified as described by Siciliano et al (2015). …”
Section: Methodsmentioning
confidence: 99%
“…Three biological replicates were conducted with at least six plants per treatment. Quantification of SA was performed as described previously [50]. …”
Section: Methodsmentioning
confidence: 99%